PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MODEL ELICITING ACTIVITIES TERKAIT KEMAMPUAN KOMUNIKASI MATEMATIS DAN MINAT BELAJAR - Ulpah, Mira; Kosasih, Usep; Saputra, Samnur (Uninus Journal of Mathematics Education and Science (UJMES), 2023)
This research is motivated by the absence of teaching tools that suit the needs of students and the low ability of mathematical communication and interest in learning. This is the main reason for the need to develop student worksheets using eliciting activities models related to mathematical communication skills and learning interest. This study aims to determine the feasibility of student worksheets developed. This research method is Research and Development with the ADDIE design. The data source in this study is an expert validator. The data collection instrument used was the expert validation sheet. Data were analyzed using percentages which were concluded according to qualifications. Based on the analysis carried out, it can be concluded that the student worksheets developed are feasible to be used for learning mathematics. It is suggested that the developed student worksheets can be an alternative teaching tool in mathematics, and it is necessary to carry out further research in order to obtain quality and general student worksheets. Keywords: student worksheets, eliciting activity models, mathematical communication skills, interest in learning.